Ethnic networks and employment outcomes - Eleonora Patacchini; Yves Zenou (Institute for the Study of Labor (IZA), 2008)
We analyse the effect of strong and weak ties on the individual probability of finding a job. Using the dynamic model of Calvó-Armengol and Jackson (2004), two results are put forward: (i) the individual probability of finding a job is increasing in the number of strong and weak ties; (ii) the longer the length of ties, the lower is this effect. We approximate the social space by the geographical space. Ethnicity is the chosen dimension along which agents' social contacts develop and, as a result, we use ethnic population density to capture social interactions within the given ethnic group. Using a panel of local authority-level data in England between 1993 and 2003, we find that (i) the higher the percentage of a given ethnic group living nearby, the higher the employment rate of this ethnic group; (ii) this effect decays very rapidly with distance, losing significance beyond approximately 90 minutes travel time.
Keywords: A14; 330; Ethnic minorities; social interactions; population density; weak and strong ties; Migranten; Arbeitsuche; Berufliche Integration; Ethnische Gruppe; Soziale Beziehungen; Wohnstandort; Bevölkerungsdichte; Großbritannien